A Case of Soft Tissue Fibroma in Wistar Rat (Rattusnorvegicus) (Indian Journal of Veterinary Pathology, 2025)
Fibromas are benign connective tissue tumours arising from fibroblasts and are occasionally observed as spontaneous neoplasms in laboratory animals. In laboratory rats (Rattusnorvegicus), fibromas are considered uncommon but may occur in aging individuals, often as incidental findings during long-term toxicity or carcinogenicity studies. Present clinical case report management of a fibroma in an 18-month-old female wistar rat. The animal presented with a firm, slow-growing, non-ulcerated mass located on the dorsal thoracic region. Clinical examination revealed hard mass in thoracic region with problem in normal feeding. The mass was surgically excised and subjected to histopathological evaluation, which showed a well-circumscribed proliferation of mature fibroblasts arranged in interwoven bundles within a dense collagenous matrix, with no evidence of mitotic activity, nuclear atypia or tissue invasion. Based on these findings, a diagnosis of fibroma was confirmed.